Second harmonic generation studies on Guanidine Nitrate added triglycine sulphate crystals (International Journal of Food and Nutritional Sciences, 2022)
The field of nonlinear optics became practically a reality after the invention of laser. High Performance electro-optic switching elements for telecommunications and optical information processing are based on materials with high nonlinear optical (NLO) properties. The development and encroachment of high technology, from transportation, computation to information is based on the availability of materials in the form of single crystals. AR grade chemicals such as glycine, sulphuric acid and Guanidine Nitrate were purchased commercially and were taken in 3:1:1 molar ratio. The reactants were dissolved using the double distilled water and a hot plate magnetic stirrer. The solution was heated for 3 hours at 60 oC for the reaction to take place. Then the solution was cooled to room temperature and filtered using a fine filter paper. The filtered solution was taken in a crystallizer for the growth of bulk crystals. The grown crystals TGSGN were harvested after a growth period of 30 days and the size of a typical grown crystal was 12 mm x 10 mm x 8 mm. The crystal structure was checked by XRD method and the grown crystal is observed to be crystallizing in monoclinic structure. The grown crystal was identified as the triglycine sulphate crystal doped with Guanidine Nitrate (TGSGN) by various studies. The SHG conversion efficiency of TGSGN crystal was found to be 0.96 times that of KDP. Thermo gravimetric analysis (TG) and differential thermal analysis (DTA) were used to study the thermal properties of the grown TGSGN crystal. The grown crystals were also subjected to FTIR, micro hardness and dielectric studies.